COMUNICACIÓN ENTRE PADRES E HIJOS EN EL DESARROLLO DE LA SEXUALIDAD EN LOS ESTUDIANTES DE LA UNIDAD EDUCATIVA “CARLOS CISNEROS”. RIOBAMBA – CHIMBORAZO. PERIODO OCTUBRE 2018 - MARZO 2019. - Contreras Villacis, Thalya Nayet (2019)
The purpose of this research was to determine the communication of the parents in the development of the sexuality of the students of 7th "B" of the educational unit "Carlos Cisneros" of the city of Riobamba, since the communication between parents and children is of great importance for their healthy development, if there is good communication between both, the children will feel more confidence towards their parents and security with themselves facilitating the acquisition of values, attitudes, positive feelings about sexuality, without leaving aside self-esteem in children . Methodologically the research work corresponds to a non-experimental cross-sectional study, by level of research is descriptive and correlated. The sample was intentional non probabilistic type established in 38 students and 38 parents of the Educational Unit "Carlos Cisneros", the instruments for data collection were surveys on communication and sexuality for both parents and children for the respective analysis of the data obtained, where could demonstrate the relationship between communication and sexuality, a student who does not talk to his parents about certain sexuality issues is unsure of himself for that reason his development in sexuality is not favorable, unlike a student with good parental communication.